2017
DOI: 10.1108/ijshe-11-2016-0200
|View full text |Cite
|
Sign up to set email alerts
|

Measuring longitudinal student performance on student learning outcomes in sustainability education

Abstract: Purpose The purpose of this paper is to describe the student learning outcomes (SLOs) for a sustainability major, evaluate faculty incorporation of the SLOs into the courses in the sustainability major curriculum and measure student performance on the SLOs from entry into the major to the senior capstone course. Design/methodology/approach Through an iterative approach with a faculty advisory committee, SLOs were developed for the sustainability major. Curriculum mapping followed by evaluation of course syll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…These different ways of incorporating ESD into the curriculum involve different degrees of sustainability development and learning. On the basis of analysis by learning outcomes, some authors have investigated the essential conditions required for ESD to be included in a curriculum (Hill and Wang, 2018), while others have evaluated the result of incorporating sustainability-related learning outcomes in different courses and the performance achieved by students (Jarchow et al , 2018). Based on a scientific literature review on sustainability, Berchin et al (2017) identified the recurrent actions for sustainability carried out in some higher education institutions and focused these actions in a case study in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…These different ways of incorporating ESD into the curriculum involve different degrees of sustainability development and learning. On the basis of analysis by learning outcomes, some authors have investigated the essential conditions required for ESD to be included in a curriculum (Hill and Wang, 2018), while others have evaluated the result of incorporating sustainability-related learning outcomes in different courses and the performance achieved by students (Jarchow et al , 2018). Based on a scientific literature review on sustainability, Berchin et al (2017) identified the recurrent actions for sustainability carried out in some higher education institutions and focused these actions in a case study in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Povećavanje produktivnosti rada nema neposredno za cilj skraćivanje dužine radnog dana, nego samo skraćivanje onog dela radnog dana u kojem radnik reprodukuje vrednost svoje radne snage (Perrault & Clark, 2017;Jarchow et al, 2018). Proizvodnja relativnog viška vrednosti ima za pretpostavku jedan specifičan način proizvodnje zasnovane na najamnom radu kojoj mora da prethodi promena u metodu organizacije proizvodnje ili različita unapređenja u sredstvima za proizvodnju.…”
Section: Pretpostavkaunclassified
“…In a rapidly changing world that is becoming increasingly complex over time, curriculum reform and improvement must be addressed in an integrated and holistic way. Higher education institutions are increasing efforts to address sustainability issues within their curricula (Jarchow et al, 2018), but the extent to how the sustainability-related topics are implemented varies between knowledge areas and educational levels and there is still room for a larger presence of sustainability in many degrees and courses (Weiss and Barth, 2019;Aleixo et al, 2020;S anchez-Carracedo et al, 2020). From this perspective, as Ferrer-Balas et al (2010) observe, to make our societies truly sustainable it may not be sufficient to introduce improvements and innovations in the way we educate; rather, it is also essential to ensure that education becomes a real tool for change.…”
Section: Introductionmentioning
confidence: 99%